Non-organ-specific autoantibodies with unspecific patterns are a frequent para-infectious feature of chronic hepatitis D - Lennart Hermanussen; Sibylle Lampalzer; Jan-Hendrik Bockmann; Jan-Hendrik Bockmann; Annerose E. Ziegler; Felix Piecha; Felix Piecha; Maura Dandri; Maura Dandri; Sven Pischke; Sven Pischke; Friedrich Haag; et al. (Frontiers in Medicine, 2023)
Infections with hepatotropic viruses are associated with various immune phenomena. Hepatitis D virus (HDV) causes the most severe form of viral hepatitis. However, few recent data are available on non-disease-specific and non-organ-specific antibody (NOSA) titers and immunoglobulin G (IgG) levels in chronic hepatitis D (CHD) patients. Here, we examined the NOSA titers and IgG levels of 40 patients with CHD and different disease courses and compared them to 70 patients with chronic hepatitis B (CHB) infection. 43% of CHD patients had previously undergone treatment with pegylated interferon-α (IFN-α). The antibody display of 46 untreated patients diagnosed with autoimmune hepatitis (AIH) was used as a reference. The frequency of elevated NOSA titers (CHD 69% vs. CHB 43%, p < 0.01), and the median IgG levels (CHD 16.9 g/L vs. CHB 12.7 g/L, p < 0.01) were significantly higher in CHD patients than in patients with CHB, and highest in patients with AIH (96%, 19.5 g/L). Also, the antinuclear antibody pattern was homogeneous in many patients with AIH and unspecific in patients with viral hepatitis. Additionally, f-actin autoantibodies were only detectable in patients with AIH (39% of SMA). In CHD patients, IgG levels correlated with higher HDV viral loads, transaminases, and liver stiffness values. IgG levels and NOSA were similar in CHD patients irrespective of a previous IFN-α treatment. In summary, autoantibodies with an unspecific pattern are frequently detected in CHD patients with unclear clinical relevance.